GAMBARAN METODE INKUIRI DAN PENERAPAN PADA PEMBELAJARAN PENGEMBANGAN DIRI (PKn) DI KELAS VI SD NEGERI NO.60 / II MUARA BUNGO KECAMATAN RIMBO TENGAH - nopriani nopriani (Jurnal Tunas Pendidikan, 2019)
The background of this study is that not all teachers in Civics learning have implemented active student-based approach learning. To create active learning, teachers can carry out learning using inquiry methods. Therefore, the purpose of this study is to describe the description of the inquiry method and its application to self-development learning (PKn) in class VI of SDN.60/II Muara Bungo, Central Rimbo District. The object of this research is Class VI students of Public Elementary School 60 /II Muara Bungo, Central Rimbo District, Bungo Regency with 30 students. The research data collection technique uses observation, interview, and test techniques. The results of this study, namely (1) Preparation of learning planning using inquiry methods covering the subject, questions that refer to conclusions, teaching aids, media, and student worksheets, (2) Learning using inquiry methods is more attractive to students and can encourage students to find the final concept (conclusion) of the observations in accordance with the time set, (3) Learning outcomes using the inquiry method is better than not using the inquiry method. (4) obstacles in conducting research can be overcome. Based on the results of the research, it can be concluded that the inquiry method can improve the process and learning outcomes of PKn students in Class VI SDN 60/II Muara Bungo, Central Rimbo District, Bungo Regency.